Perencanaan Sistem Kelistrikan PLTMH Banjar Dinas Mekar Sari - Yanto, I Putu Eka April; Giriantari, I. A. Dwi; Ariastina, W. G. (Majalah Ilmiah Teknologi Elektro, 2021)
Abstract - This paper introduces a redesign of Micro Hydro Power Plant (MHPP) in Banjar Dinas Mekar Sari, Panji Village, District of Sukasada, Buleleng Regency, Bali. The MHPP has been operated since 1980 by utilizing waterflow of Tukad Pasut River. Early investigation indicated that there is a reduced production capacity of the MHPP due to lack of maintenance. In addition, the initial design of the MHPP has not adopted the advanced power control systems, resulting in inefficient power production. The introduced design of the new MHPP utilizes a crossflow turbine to accommodate a waterflow rate of 1,32 m 3 /s and with an effective head of 16 m. The turbine mechanical energy is coupled to a generator by means of a belt coupling system, with a belt length of 3099 mm. The pulley diameter is 750 mm for the turbine side, and it is 149 mm for the generator side. The generator capacity is 185 kVA, 50 Hz, 230/400 V, 1500 rpm, and with an efficiency of 94%. The Electronic Load Controller has a capacity of 180 kW, with 6 ballast loads of 30 kW. The connection from the generator to the transformer uses the NYFGbY underground cable of 4 × 95 mm 2 , with a length of 69 m. The transformer is a step-up and step-down type with a capacity of 250 kVA.